2021
DOI: 10.1038/s41598-021-02186-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patient related factors associated with Extended-Spectrum Beta-Lactamase producing Escherichia coli and Klebsiella pneumoniae carriage and infection among pediatric patients in Tanzania

Abstract: Extended-Spectrum Beta-Lactamase (ESBL) producing Enterobacteriaceae (EPE) is increasing worldwide, though less documented in low-income settings. Here we determined the prevalence of EPE infection and carriage, and patient factors associated with EPE-carriage among pediatric patients in three health care levels in Tanzania. Between January and April 2016, 350 febrile children (median age 21 months) seeking care at a university or a regional referral hospital, or a health centre in Moshi municipality, Tanzania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
2
9
1
1
Order By: Relevance
“…Furthermore, in a different part of the city, location 2 in Tehran with lower economic income and many immigrants had significantly high EPE carriers. Therefore, this area of the city has to be taken into account because the accommodation of high population density, a high proportion of immigrant residents, and the people of a lower socioeconomic class can affect the incidence of EPE carriage (35).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a different part of the city, location 2 in Tehran with lower economic income and many immigrants had significantly high EPE carriers. Therefore, this area of the city has to be taken into account because the accommodation of high population density, a high proportion of immigrant residents, and the people of a lower socioeconomic class can affect the incidence of EPE carriage (35).…”
Section: Discussionmentioning
confidence: 99%
“…After finding an unexpectedly high prevalence of ESBL-E. coli faecal carriage in healthy subjects (>90%) in rural South Niger [14], we analysed the population structure, molecular support of resistance and mode of spread of these commensal strains in this community, using state-of-the-art sequencing techniques with both Ilumina WGS and an additional long-read sequencing by Nanopore (to specifically study strains with ESBL-encoded genes embedded in plasmids). Previous description of ESBL carriage in African settings has varied by the region, the community and the age of the subjects [2][3][4][5]12,13], ranging from 46 % in district hospital patients in South Africa in 2018 [3], 51% in hospitalized patients and 38% in healthy healthcare workers in Chad in 2019 [13], and 59% in healthy children in the community in the Central African Republic [12]. When resistance mechanisms and phylogenetic groups were described, bla CTX-M-15 was the most commonly encountered gene encoding for resistance to β-lactams (ranging from 75% to 90% of cases), and the clonal group ST131 was predominant among phylogroup B2 E. coli [12,13,15,25].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of ESBL-E. coli faecal carriage in humans is a good indicator of the global burden of antibacterial resistance in a given community [11]. In Africa, the few available studies showed a prevalence of ESBL-E. coli community faecal carriage ranging from 15% to 92% depending on the country, the population studied and the year of stool collection, which is higher than in most high income countries [2][3][4][5][12][13][14]. However, little is known about the molecular epidemiology and evolution of resistance mechanisms in low-income countries [13,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las enterobacterias productoras de BLEE predominan cada vez más a nivel mundial y varían en diferentes áreas geográficas (19). Se caracterizan por ser bacilos gramnegativos que pertenecen a la familia Enterobacteriaceae, tales como, Klebsiella pneumoniae, Escherichia coli, Proteus mirabilis, Serratia spp., Salmonella spp., etc.…”
Section: Discussionunclassified